2016
DOI: 10.1016/j.nucengdes.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Surrogates based multi-criteria predesign methodology of Sodium-cooled Fast Reactor cores – Application to CFV-like cores

Abstract: The Sodium-cooled Fast Reactor (SFR) core predesign process is commonly realized on the basis of expert advices and local parametric studies. As such, in-deep knowledge of physical phenomena avoids an important number of expensive simulations. However, the study space is explored only partially. To ease the computational burden metamodels, or surrogate models, can be used, to quickly evaluate the performances of a wide set of different cores, individually defined by a set of parameters (pellet diameter, fissil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…This could not have been concluded by considering only the Doppler feedback and total sodium void worth. These results are consistent with the findings in (Fabbris et al, 2016). It can be observed in Table 5 that these results do not appear to depend on the transient considered.…”
Section: Ulofsupporting
confidence: 92%
See 1 more Smart Citation
“…This could not have been concluded by considering only the Doppler feedback and total sodium void worth. These results are consistent with the findings in (Fabbris et al, 2016). It can be observed in Table 5 that these results do not appear to depend on the transient considered.…”
Section: Ulofsupporting
confidence: 92%
“…3. This approach was previously used in (Fabbris et al, 2016) in combination with the more detailed CATH-ARE code (Emonot et al, 2011) and it was shown to introduce limited errors on the temperature profile in the core (below 5°C). Doppler and sodium thermal expansion profiles were similarly averaged over each medium, with the sodium and plenum sodium thermal expansion being added in an extra mesh on top of the fissile stack with zero power generation.…”
Section: Core Description and Calculations Toolsmentioning
confidence: 99%
“…This factor is a measure of how well the meta-models reproduce the variance of the actual model. A meta-model will be deemed acceptable if the Q 2 estimator is higher than 0.95 in this context [15]. As it is shown in Table 3, it can be observed that all the estimators studied here exhibit higher than 0.95 Q 2 values, thus validating their good behavior.…”
Section: Description Of the Optimization Processsupporting
confidence: 53%
“…18 Considering the computational burden of Monte Carlo calculations, surrogate models are generated for neutronic design evaluation during the optimization process. 19 Nevertheless, safety concerns like material structural feasibility are not considered, 20 and a significant discrepancy is found in the void worth prediction. 21 Meanwhile, direct Monte Carlo simulations are used for some core optimization studies, in which the optimization objectives and corresponding input parameters are relatively less.…”
Section: Introductionmentioning
confidence: 99%